DAMPAK COVID-19 TERHADAP PERUBAHAN HARGA SAHAM DAN VOLUME TRANSAKSI SAHAM SYARIAH (STUDI KASUS PADA PT. UNILEVER, TBK) - Dian Nilam Sari; Yolanda Wahyu Lestari (J-EBI (Jurnal Ekonomi Bisnis Islam), 2022)
COVID-19 is the latest virus that appeared around December 2019 in Wuhan, China. The virus is spreading rapidly in various parts of the country, including Indonesia. This virus that spreads in Indonesia breaks the myth of